CARING KELUARGA DENGAN KEJADIAN JATUH PADA LANSIA (Family Caring And Fall Incident On Eldery) - ISWATI, . (JURNAL NERS LENTERA, 2017)
Introduction: The progress in the health sector, the increasing welfare of the people can increase life expectancy, causing the number of the elderly population to increase every year. Seniors experience a decrease in the body's ability to adapt to the environment, so the risk of falling. Caring a family is what the elderly needs to prevent injuries and trauma from falling. Method: This research is correlation research by using cross sectional approach. The independent variable is caring family, while the dependent variable is the fall incident. Sampling was done in RW 07 Kelurahan Gading Kecamatan Tambaksari Surabaya by using technique "Simple Random Sampling" with the amount of sample is 45 respondents. Data were collected using questionnaire, data analysis with Chi Square statistical test. Results: Showing 32 respondents (71.1%) stated that caring in good family, 29 (64.4)% did not fall. Chi Square = 0,000 with α = 0.05, Discussion and conclusion: The relationship between caring family with incidence of fall in elderly, the family caring can influence the incidence of fall in the elderly, the researcher then consider the elderly expectations according to the criteria so that the results are expected to be more accurate .